The roles of good governance to sustain health waqf: A scoping review - Nurul Aien, Abd Aziz; Noraina Mazuin, Sapuan; Puteri Fadzline, Muhamad Tamyez; Nurliana, Nasution (Universiti Malaysia Pahang, 2025)
Good governance is essential for maintaining the efficiency and sustainability of health waqf. The research systematically examines the literature to comprehend the impact of governance structures on the administration and efficiency of health waqf. The study analyses the influence of stakeholder participation, trust, and asset protection on the operation and sustainability of Islamic charitable institutions. This scoping review fills this gap using an advanced search method on the Scopus database, including papers published up to 2023. The inclusion criteria included empirical research and systematic reviews examining good governance’s roles in sustaining health waqf. Stakeholder engagement is crucial for aligning health waqf resources with community needs and principles, as shown by the results. Involvement of donors, recipients, waqf administrators, and governmental authorities guarantees open and ethical decision-making, promoting confidence at all levels. This trust is not only a passive belief but a strong basis that greatly improves the ability of waqf organizations to attract additional donations and broaden their healthcare projects. Maintaining waqf assets is essential to ensure the health of waqf's durability. Utilizing innovative solutions such as waqf-based Islamic microfinance and multi-sectoral asset management is necessary for improving health waqf's financial stability and long-term efficiency. This research contributes to enhancing governance to strengthen the administration and execution of health waqf in the future.